PENGARUH GAYA KEPEMIMPINAN, LINGKUNGAN KERJA, DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA PEGAWAI DINAS PENDIDIKAN PROVINSI DKI JAKARTA - VIRGANA, VIRGANA (JURNAL ILMIAH EDUCATIONAL MANAGEMENT, 2011)
This causal research aims to assess the direct and indirect effect of the leadership style, work environment, and employeesâ work motivation on the job satisfaction of the employeesâ of the Education Office of the DKI Jakarta Province. The data were collected from a randomly selected sample of 100 employees of the education of the DKI Jakarta Province of Rank (Golongan) III, through a three-month survey from March 2009 with a questionnaire consisting of questions with Liker scale choices. A path technique was employed to analyse the data descriptively and inferentially. The findings show (1) a direct effect of the leadership style on the employeesâ work motivation, (2) a direct effect of the environment on the employeesâ work motivation, (3) a direct effect of the leadership style on the employeesâ job satisfaction, (4) a direct of the work environment on the employeesâ job satisfaction, (5) a direct effect of the work environment on the employeesâ job satisfaction, (6) an indirect effect of the leadership style on the employeesâ job satisfaction, and (7) an indirect effect of the work environment on the employeesâ satisfaction. These findings suggest that the leadership style, work environment, and work motivation are determining factors of the employeesâ job satisfaction, hence the need to take them into consideration in the development of human resource.Keywords: leadership style, work environment, work motivation on the job satisfaction